Socioeconomic Inequalities in Out-of-Pocket and Catastrophic Health Expenditures in Pakistan - Saima Bashir; Shabana Kishwar; Muhammad Nasir; Shehzad Ali (Frontiers Media S.A., 2024)
ObjectivesIn Pakistan, healthcare utilization is linked to out-of-pocket payments (OOP) which disproportionately affect low-income households. We investigated socioeconomic inequality in OOP and catastrophic health expenditures (CHEs), and the contribution of sociodemographic factors to these inequalities.MethodsSocioeconomic inequalities were quantified using the concentration index (CI), and the slope (SII) and relative (RII) indices of inequality using data from three rounds of Household Integrated Economic Survey (2007-08, 2011-12, and 2018-19). Decomposition analyses were conducted using the Wagstaff and Erreygers approach.ResultsOOP payments increased from PKR 127 (2007-08) to PKR 250 (2018-19). CHEs in the most deprived quintile (Q1) changed from 8.3% (2007-08) to 13.7% (2018-19), and for the least deprived quintile (Q5) from 5.1% (2007-08) to 8.4% (2018-19). The OOP CI increased from 0.028 to 0.051, while the SII and RII increased from 0.89 to 1.32 and 1.18 to 1.36, respectively. Decomposition analysis showed that household size, composition, employment, and the province of residence explained much of the socioeconomic inequality in CHEs.ConclusionPoor households experience high CHE, disproportionately impacting larger families with children and elderly members. Policymakers should implement targeted financial protection strategies to safeguard vulnerable households from the impoverishing effects of healthcare expenses.